Karakteristik Organoleptik dan Daya Terima Kukis Lidah Kucing dengan Substitusi Tepung Biji Labu Kuning dan Tepung Hati Sapi - Brilian Callista Karunia; Annis Catur Adi (Lembaga Pengembangan Kinerja Dosen, 2026)
Iron deficiency anemia remains a prevalent nutritional problem in Indonesia, with a prevalence of 15.5% among adolescent girls aged 15–24 years based on the 2023 Indonesian Health Survey (SKI). This study aimed to analyze the organoleptic characteristics and acceptability of lidah kucing cookies with yellow pumpkin seed flour and beef liver flour substitution as an alternative snack for anemia-prone adolescent girls. This study used a true experimental design with a Completely Randomized Design (CRD), consisting of four formulas: F0 (100% wheat flour), F1 (50%:40%:10%), F2 (50%:35%:15%), and F3 (50%:30%:20%), representing proportions of wheat flour, yellow pumpkin seed flour, and beef liver flour respectively. Organoleptic quality testing was conducted by 3 limited panelists, while hedonic testing was conducted by 30 untrained panelists aged 14–16 years. Statistical analysis used the Shapiro-Wilk test for normality and the Friedman test for differences in acceptability among formulas. Results showed that F1 had the best organoleptic quality characteristics, with a yellowish-green color, slightly fishy aroma, crunchy and slightly coarse texture, and slightly sweet taste with a faint fishy aftertaste. The Friedman test indicated significant differences (p<0.05) in color, aroma, taste, and overall acceptability among formulas, but not in texture (p=0.061). F1 obtained the highest acceptability for color, texture, and overall parameters, while F3 obtained the highest acceptability for aroma. F1, with proportions of 50% wheat flour, 40% yellow pumpkin seed flour, and 10% beef liver flour, was determined as the most optimal formula among all modified formulas.